Результати експериментальних досліджень пневматичного збирання шкідників сільськогосподарських культур - Онопа, В. А.; Артеменко, Д. Ю.; Onopa, V.; Artemenko, D. (ЦНТУ, 2022)
В статті наведені результати експериментальних досліджень пневматичного збирання шкідників сільськогосподарських культур. На сьогоднішній день комахи-шкідники є однією з головних проблем у сільському господарстві. Шкідники щороку спричиняють від 20 до 40 відсотків втрат світового виробництва сільськогосподарських культур, основним методом боротьби з якими є пестицидна обробка. Безперервне використання пестицидів призводить до потенційних людських захворювань, забруднення рослин і ґрунту, тому велика увага приділена методам екологічної боротьби. Пневматичне збирання шкідників є основним і максимально ефективним засобом боротьби. А розробка нових конструкцій і пристроїв для його виконання є актуальною задачею. В роботі запропонована конструкція пневмодезинсектора для пневматичного збирання шкідників сільськогосподарських культур та досліджена ефективність його роботи. Експериментальні дослідження запропонованого пневмодезинсектора показали, що в середньому за триразовий збір ефективність становила: на озимій пшениці - 74,0%, на люцерні – 60%, на картоплі 68,3%, на баклажанах – 78,5%, на томатах – 79,3%, на перці солодкому – 91,0%. Кількість рослин, уражених вірусами, зменшилася у 1,2 рази порівняно з контролем без пневмодезинсекції. Витрати застосування хімічного захисту перевищували витрати на пневмодезинсекцію в 4,7 рази. The article presents the results of experimental research on the pneumatic collection of pests of agricultural crops. Today, insect pests are one of the main problems in agriculture. Pests cause 20 to 40 percent of global crop losses every year, and pesticide treatment is the main method of control. The continuous use of pesticides leads to potential human diseases, plant and soil pollution, so much attention is paid to ecological control methods. Pneumatic collection of pests is the main and most effective means of control. And the development of new designs and devices for its implementation is an urgent task. The analysis of the constructions and researches of pneumatic machines for harvesting pests of agricultural crops allowed us to come to the conclusion that recently, machines with a pneumatic harvesting system are most often used for harvesting pests, as those that damage the plant the least. Due to their efficiency, pneumatic machines of the suction type are becoming the most popular. The use of machines of this type will make it possible to obtain ecologically clean food products without the use of chemical means of control. In the work, the design of the pneumodisinfector and the device for the pneumatic collection of pests of agricultural crops is proposed and the efficiency of its operation is investigated. Experimental studies of the proposed pneumodisinfectant sector showed that, on average, for three harvests, the effectiveness was: on winter wheat - 74.0%, on alfalfa - 60%, on potatoes - 68.3%, on eggplant - 78.5%, on tomatoes - 79, 3%, sweet pepper – 91.0%. The number of plants affected by viruses decreased by 1.2 times compared to the control without pneumodisinfection. The costs of applying chemical protection exceeded the costs of pneumodisinfection by 4.7 times. On the basis of the obtained data, in the conditions of production crops of winter wheat, alfalfa, eggplant and potatoes, the use of a pneumodisinfector is an effective method.
Results of Experimental Studies Pneumatic Harvesting of Pests Agricultural Crops
Keywords: шкідники сільськогосподарських культур; пневматичне збирання шкідників; пристрій для збирання; пневмодезинсектор; екологічний захист рослин; pests of agricultural crops; pneumatic collection of pests; device for collection; pneumodisinsector; environmental protection of plants